MUC1 alleviates PM2.5-induced airway inflammation by inhibiting the IRAK4/NF-κB/NLRP3 mediated pyroptosis in airway epithelial cells - Zhou, You; Yang, Kai; Wang, Jian; Guan, Ruijuan; Liu, Wei; Wen, Chaowei; Yuan, Liang; Zhang, Tiange; Feng, Wei; Li, Yuanyuan; Xu, Jingyi; Lu, Wenju (Frontiers in Immunology, 2025)
BackgroundsExposure to fine particulate matter (PM2.5) triggers airway inflammation through the activation of the Toll-like receptor 4 (TLR4)/nuclear factor-κB (NF-κB) signaling pathway, contributing to the pathogenesis of various acute and chronic respiratory diseases. Mucin 1 (MUC1), a transmembrane glycoprotein highly expressed on airway epithelial cells, is known to modulate TLR-mediated inflammatory responses. However, the specific role and molecular mechanism by which MUC1 regulates PM2.5-induced airway inflammation remain inadequately understood.MethodsLung injury models were established using Muc1+/+ and Muc1-/- rats via intranasal instillation of PM2.5. Histopathological changes and inflammatory responses were evaluated following treatment. In parallel, human bronchial epithelial cells (16HBE) were transfected with MUC1 overexpression and knockdown plasmids, along with corresponding controls. An IRAK4-specific inhibitor was employed to explore the mechanistic role of MUC1 in regulating the TLR4/IRAK4/NF-κB signaling cascade and associated pyroptosis.ResultsPM2.5 exposure caused notable epithelial disruption, inflammatory infiltration, and submucosal fibrosis in Muc1-/- rats compared to Muc1+/+ controls. While TLR4 expression was not significantly altered, NF-κB and NLRP3 inflammasome activity were markedly elevated in Muc1-deficient rats. In 16HBE cells, MUC1 overexpression attenuated, whereas MUC1 knockdown exacerbated, PM2.5-induced activation of the IRAK4/NF-κB signaling axis and pyroptosis-related markers (IL-1β, IL-18, NLRP3, GSDMD). Furthermore, pharmacological inhibition of IRAK4 mitigated these effects, confirming the involvement of the IRAK4 pathway in MUC1-mediated protection.ConclusionsMUC1 is upregulated in airway epithelial cells upon PM2.5 exposure and serves as a key endogenous inhibitor of airway inflammation. It exerts its anti-inflammatory and anti-pyroptotic effects by suppressing IRAK4 phosphorylation, thereby modulating downstream NF-κB/NLRP3/GSDMD signaling. These findings highlight MUC1 as a potential therapeutic target for PM2.5-induced airway inflammatory diseases.